2009
DOI: 10.1302/0301-620x.91b2.20473
|View full text |Cite
|
Sign up to set email alerts
|

The use of the cemented Exeter Universal femoral stem in a District General Hospital

Abstract: We describe the survivorship of the Exeter femoral component in a District General Hospital. Between 1994 and 1996, 230 Exeter Universal cemented femoral components were implanted in 215 patients who were reviewed at a mean of 11.2 years (10 to 13). We used one acetabular implant, the Elite Ogee component, in 218 of the 230 hips. During the period of this study 76 patients (79 hips) died. Of the remaining 139 patients (151 hips), 121 were able to attend for radiological analysis at a minimum of ten years. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
4
20
2
Order By: Relevance
“…We found cementless or cemented primary THA prostheses designs had no correlation with revision probability. The literature seems to agree with these data showing comparable revision rates after THA implantation of cemented or cementless implants in the general population [24,39]. In patients younger than 30 years, with 6 years' followup, Restrepo et al [29] reported only one revision with cementless implants, with excellent bone stock ongrowth.…”
Section: Discussionsupporting
confidence: 54%
“…We found cementless or cemented primary THA prostheses designs had no correlation with revision probability. The literature seems to agree with these data showing comparable revision rates after THA implantation of cemented or cementless implants in the general population [24,39]. In patients younger than 30 years, with 6 years' followup, Restrepo et al [29] reported only one revision with cementless implants, with excellent bone stock ongrowth.…”
Section: Discussionsupporting
confidence: 54%
“…Our stem survival of 100% is consistent with the published studies of cemented polished double-taper stems in similarly aged patients [3,6,21,32] (Table 3). Importantly, these survival rates in young patients often with complex hip disorders were also comparable to those for longer-term followups of this stem design in older patients [3,6,10,16,21,32,37] (Table 3). Lewthwaite et al [21] reported 17-year stem survivals of 100% and 99% for the end points of revision for stem loosening and for any reason, respectively, in young patients.…”
Section: Discussionsupporting
confidence: 55%
“…14,29,30 This is in stark contrast to the Exeter design, from which the CPT was derived, which has excellent clinical and radiological followup in both its originating centre [1][2][3][4][5] and elsewhere. 6,7 This study follows the same cohort of patients previously reported at a minimum of ten years post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…The impressive survival of collarless polished double tapered femoral components has been demonstrated in originator series, [1][2][3][4][5] in nonoriginator series 6 and non-teaching centres 7 and in registry data. 8,9 There have been predictable patterns of subsidence at the stemcement interface, 10 a factor that has been suggested to confer stability to the stem 11 and provide protection to the cement-bone interface.…”
mentioning
confidence: 99%